Reformation of the repair and maintenance system of aircraft engineering - Podreza, S. M. (Proceedings of National Aviation University (archive), 2003)
Questions of re-structuring of support and maintenance system of planes serviceability of new generation are considered. Variants of creation and development of concern Aviatechservice are offered